2008
DOI: 10.1007/s10663-008-9082-3
|View full text |Cite
|
Sign up to set email alerts
|

When and why do Austrian companies issue shares?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Consistent with these results are findings of a survey conducted by Burgstaller (2005). He examined public issues on the Vienna Stock Exchange between 1985 and 2004.…”
Section: Theoretical Frameworksupporting
confidence: 57%
“…Consistent with these results are findings of a survey conducted by Burgstaller (2005). He examined public issues on the Vienna Stock Exchange between 1985 and 2004.…”
Section: Theoretical Frameworksupporting
confidence: 57%
“…Moreover, it covers all the IPO activity that occurred in all European countries during the same period. Existing literature in this field mainly focuses on a specific country (e.g., Burgstaller [] in Austria, Huyghebaert and Van Hulle [] in Belgium, and Pagano, Panetta, and Zingales [] in Italy), with different methodologies and different time periods. This fact makes the comparison between them difficult, if not impossible.…”
Section: Introductionmentioning
confidence: 99%
“…Similar evidences have been reported in several other studies as well. For instance, Ritter (1984); Loughran and Ritter (1995); Ritter and Welch (2002); Rajan and Servaes (1995)and Burgstaller (2003) documented that firms time the issue of equities to take advantage of favourable market conditions. However, hot issue market not necessarily coincide with urgent fund requirements or future investment opportunity (Loughran et al 1994).…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…It is usually more attractive for issuers to raise capital during the period of high stock market valuation due to the low cost of equity owing to the high investor optimism. Burgstaller (2009) found that prevailing interest rates and corporate indebtedness are significant determinants of seasoned equity offerings in both statistical and economic terms. Results of a survey with 336 CEOs conducted by Brau and Fawcett (2004) confirms that prevailing market condition plays a crucial role in timing the public offering.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation